Beyond language deficiency: Students’ code-switching in International Program of Vocational Higher Education in Indonesia - Hilda Cahyani; Isnaini Nur Safitri (Pascasarjana UM, 2021)
Abstract: Code-switching (switching in-and-out from one language to another) has been an international debate whether it is a simply language avoidance or a communication strategy. It is thus crucial to see in what way and in what situations students made use code-switching in the classroom. The study was conducted in an English Medium Instruction at vocational tertiary level in East Java, Indonesia involving six students in the classroom observation and semi-structured interview in three content-subject classrooms. This study reported that students’ code-switching functioned for transmitting information to their peers, managing their interaction and building interpersonal relations. This study argues that code-switching is not merely done due to a language deficiency rather is an intentional strategy to make a meaningful communication. Students’ code-switching also showed a collectivist behaviour among the participants when their switching into a particular language for showing solidarity and concern to their peers. Key Words: students’ code-switching; international program; vocational higher education; Indonesia Abstrak: Alih kode atau yang disebut peralihan bahasa satu telah menjadi perdebatan untuk membuktikan apakah alih kode ini merupakan pengalihan karena ketidakpampuan dalam berbahasa ataukah strategi dalam berkomunikasi. Sangat penting untuk mengkaji dengan cara apa dan dalam situasi apa siswa menggunakan alih kode di dalam kelas. Penelitian ini dilakukan di kelas bilingual pada satu perguruan tinggi vokasi di Jawa Timur, Indonesia dengan melibatkan enam mahasiswa untuk observasi di kelas dan wawancara semi-terstruktur di tiga kelas bilingual. Studi ini melaporkan bahwa alih kode mahasiswa berfungsi untuk bertukar informasi dengan teman sebayanya, melakukan interaksi diantara mereka dan menjalin hubungan interpersonal. Temuan studi ini menunjukkan bahwa alih kode tidak semata-mata dilakukan karena keterbatasan dalam berbahasa, melainkan merupakan strategi dalam berkomunikasi. Penelitian ini melaporkan bahwa alih kode yang dilakukan mahasiswa juga menunjukkan perilaku kolektivis di antara mereka. Menariknya alih kode tertentu dilakukan untuk menunjukkan solidaritas dan kepedulian kepada teman sejawat mereka.Kata Kunci: alih kode mahasiswa; program internasional; perguruan tinggi vokasi; Indonesia